Optimal operation strategy for distribution network with high penetration of dispersed wind power - Duan, Jiandong; Chen, Lupeng; Lu, Wenchao; Zhu, Darui; Sun, Qian (Frontiers in Energy Research, 2023)
As a significant approach to local utilization of clean renewable energy, the dispersed wind power (DWP) is becoming more and more widespread in engineering applications. With the fluctuating wind power widely and dispersedly integrated into distribution networks, it is urgent and pressing to effectively enhance the penetration rate of wind power based on the safe operation of distribution networks. This paper takes full advantage of the power regulation ability of wind turbines to actively participate in the operation of distribution networks, and then an optimal operation model of distribution networks is established with the optimization objectives of high penetration of DWP and maximum correntropy of node voltage. Aiming at the characteristics of the proposed model, the multi-objective brain storm optimization algorithm is adopted to solve the model to achieve the Pareto solution set, and the fuzzy membership function is used to determine the optimal operation scheme from the solution set. The simulation results on the expanded IEEE 33 bus system indicate the rationality of the proposed optimal operation strategy of distribution networks with high penetration of DWP. Meanwhile, the feasibility of the optimal operation scheme is verified through the case of a practical demonstration project.